Streptomyces sp. AN090126 as a Biocontrol Agent against Bacterial and Fungal Plant Diseases - Khanh Duy Le; Nan Hee Yu; Ae Ran Park; Dong-Jin Park; Chang-Jin Kim; Jin-Cheol Kim (Microorganisms, 2022)
Bacteria and fungi are major phytopathogens which substantially affect global agricultural productivity. In the present study, Streptomyces sp. AN090126, isolated from agricultural suppressive soil in Korea, showed broad-spectrum antagonistic activity against various phytopathogenic bacteria and fungi. In the 96-well plate assay, the fermentation filtrate of Streptomyces sp. AN090126 exhibited antimicrobial activity, with a minimum inhibitory concentration (MIC) of 0.63–10% for bacteria and 0.63–3.3% for fungi. The MIC of the partially purified fraction was 20.82–250 µg/mL for bacteria and 15.6–83.33 µg/mL for fungi. Gas chromatography–mass spectrometry (GC-MS) analysis revealed that AN090126 produced various volatile organic compounds (VOCs), including dimethyl sulfide and trimethyl sulfide, which inhibited the growth of pathogenic bacteria and fungi in in vitro VOC assays. In pot experiments, the fermentation broth of Streptomyces sp. AN090126 reduced tomato bacterial wilt caused by Ralstonia solanacearum, red pepper leaf spot caused by Xanthomonas euvesicatoria, and creeping bentgrass dollar spot caused by Sclerotinia homoeocarpa in a dose-dependent manner. Moreover, the secondary metabolites derived from this strain showed a synergistic effect with streptomycin sulfate against streptomycin-resistant Pectobacterium carotovorum subsp. carotovorum, the causative agent of Kimchi cabbage soft rot, in both in vitro and in vivo experiments. Therefore, Streptomyces sp. AN090126 is a potential biocontrol agent in controlling plant diseases caused by pathogenic bacteria and fungi, specifically by the streptomycin-resistant strains.